Skandal Suap Hakim Kasus Ekspor CPO: Saatnya Korporasi Bertanggung Jawab - Gilang Cahya Buana; Nabila Nurapitasari; Herawati Barkah; David Nugraha Saputra (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The palm oil industry is a strategic sector that significantly contributes to Indonesia's economy through crude palm oil (CPO) exports. However, it is also prone to corruption practices, as revealed in the bribery case involving a judge in the handling of a CPO export trial. This scandal highlights corporate involvement in influencing court decisions for business interests and the weak law enforcement against corporations as the main perpetrators of criminal acts. This paper aims to analyze the chronology and modus operandi of the bribery, identify factors behind the weak corporate criminal liability enforcement, and formulate recommendations to strengthen the legal system to prevent similar cases in the future. The research method used is normative juridical with statutory and case approaches. The data is analyzed qualitatively to assess the effectiveness of regulations and the obstacles in implementing corporate criminal liability. This study is expected to contribute to reforming a fairer and more accountable legal system in strategic economic sectors.